Polishing Papers for Publication: Palimpsests or Procrustean Beds? - Bennett, Karen (2012)
This chapter is the result of a collaboration between a corpus linguist and a polisher or reviser of academic papers written by established Portuguese academics. The aim was to examine the hypothesis that not only lexical and syntactic features, but also phraseological and discourse features of L1 may be transferred into the Portuguese researchers’ L2 writing, thereby undermining the “naturalness” of the writing and raising an (invisible?) obstacle to international publication. The corpus (Portac), which consisted of some 113,000 running words of English academic prose, was created from texts that had been presented to the language consultant for revision prior to submission for publication. After correction of superficial grammatical and spelling errors, it was tagged for Part of Speech (CLAWS7) and semantic field (USAS) using WMatrix2 (Rayson 2003), and interrogated for the presence of certain discourse features using Wmatrix2 and Wordsmith Tools (Scott 1999). The findings were then compared with those of a control corpus (Controlit) of published articles written by L1 academics in a similar field. The results reveal significant overuse of certain features by Portuguese academics, and a corresponding underuse of others, suggesting a marked disparity in the value attributed to those features by the two cultures. This, it is suggested, may be due to differences in epistemological outlook, which raises issues of both a practical and an ideological nature for the language reviser.